CONDITIONS OF CIVIL-LAW AGREEMENT: NOTION, TYPES, SIGNIFICANCE - Yu. A. Serkova (Russian Journal of Economics and Law, 2007)
The article analyzes the traditional for civilistics classifications of civil-law agreements conditions, with the special emphasis on the essential conditions division into various groups. The agreement object is viewed separately as the individualizing essential condition. The author's classification of agreement conditions is suggested.